Noninvasive Manganese-Enhanced Magnetic Resonance Imaging for Early Detection of Breast Cancer Metastatic Potential - Joris Tchouala Nofiele; Gregory J. Czarnota; Hai-Ling Margaret Cheng (Molecular Imaging)
Cancer cells with a high metastatic potential will more likely escape and form distant tumors. Once the cancer has spread, a cure is rarely possible. Unfortunately, metastasis often proceeds unnoticed until a secondary tumor has formed. The culprit is that current imaging-based cancer screening and diagnosis are limited to assessing gross physical changes, not the earliest cellular changes that drive cancer progression. The purpose of this study is to develop a novel noninvasive magnetic resonance (MR) cellular imaging capability for characterizing the metastatic potential of breast cancer and enable early cancer detection. This MR method relies on imaging cell uptake of manganese, an endogenous calcium analogue and an MR contrast agent, to detect aggressive cancer cells. Studies on normal breast epithelial cells and three breast cancer cell lines, from nonmetastatic to highly metastatic, demonstrated that aggressive cancer cells appeared significantly brighter on MR as a result of altered cell uptake of manganese. In vivo results in nude rats showed that aggressive tumors that are otherwise unseen on conventional gadolinium-enhanced MR imaging are detected after manganese injection. This cellular MR imaging technology brings a critically needed, unique dimension to cancer imaging by enabling us to identify and characterize metastatic cancer cells at their earliest appearance.